Pertanggungjawaban Pidana Partai Politik Dalam Tindak Pidana Korupsi Di Indonesia - Waas, Armelia Febryanti (MATAKAO Corruption Law Review, 2023)
Introduction: Corruption is a serious problem in Indonesia. Corruption is like a disease that appears one after another, which can bring destruction to the economic, political, socio-cultural, and security aspects of the country. Recently, several cases have shown that corruption involves political parties, but no political party has yet been charged. The purpose of writing this scientific journal is to provide knowledge about how political parties can be equated with corporations and how they are held accountable when proven to have committed a criminal act of corruption. Purposes of the Research: To analyse the criminal liability of political parties in corruption offences. Methods of the Research: The research method used is normative juridical, with a statutory and conceptual approach. The sources of legal materials used are primary, secondary, and tertiary legal materials. Results of the Research: The analysis shows that political parties are the same as corporations. This is viewed from the aspect of the characteristics and concepts of the existing statutory provisions, namely the law on eradicating criminal acts of corruption and the law on political parties. Regarding the liability that can be requested to corporations proven to have committed acts of corruption, it refers to the Criminal Code except death penalty, imprisonment and confinement. In addition, the Law on the Eradication of Corruption also provides for the imposition of a maximum fine plus one-third. So that based on the concept of responsibility can be used as a guideline by law enforcers in eradicating corruption in Indonesia.